PENGARUH PERBEDAAN MATA JARING GILL NET LINGKAR (ENCIRCLING GILL NET) TERHADAP CARA TERTANGKAP IKAN KEMBUNG PEREMPUAN (Scomber negletus) DI PELABUHAN PERIKANAN PANTAI (PPP) TAWANG KABUPATEN KENDAL - Hargyandaru, Hanung; M.Pi., Asriyanto; M.Pi., Pramonowibowo (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Tawang waters have a high potential of fisheries which one of them is short bodied mackerel fishery. Potential sustainable utilization of mackerel in Kendal began to dominate the total production each year exceeds the number of other species of annual fish production as in the year 2009 with 55.222 kgs, in 2010 with 98.263 kgs and 81.027 kgs in 2011. The use of gill nets has been known for a long time by fishermen in Coastal Fishery Port of Tawang for catching short bodied mackerel, according to the fisherman of Tawang, the fish catched using mesh size 2” gill net is perceived less optimal for them. The goal of this research is to find out and analyze the use of different mesh sizes, the different of the way short bodied mackerel caught and the interaction between the mesh size and catching way to the short bodied mackerel (Scomber negletus) caught in Tawang Waters. This research was held from September to October 2012 in Tawang Waters, Kendal District, Central Java Province. This research uses experimental fishing method. The data analysis uses one Way Anova with the support of SPSS 19.0 program. The result of this research shows that the use of different mesh size affects to the fish catch, that mesh size 1.75” scores higher. There is a significant difference in amount and weight of caught fish by gilled and entangled way from the total short bodied mackerel (Scomber negletus) caught, which more fish caught by using gilled than entangled way. There is also an interaction effect between the difference of mesh size 1.75” and 2” and the difference way of caught using gilled and entangled to the catch of short bodied mackerel.